Developing efficient software solution while considering the environment - Aboubakar Idriss, Hissein; Ahmad Dahlan, Abdul Rahman (University Sultan Zainal Abidin, 2011)
"Green" information technology has become a popular and trendy topic. Many companies are exploring methods, practices and policies to use green application development techniques. Energy consumption is a major cost of operating IT software in organizations and data centers. Hardware and software developers and manufacturers are beginning to include power saving options and strategies during project planning to reduce energy consumption and e-waste. While, software solutions are considered a valuable item in the IT project, there has been less research conducted to highlight their impact on the green technology movement. This paper focuses on the impact of developing green software solution on energy utilization and its benefits for the environment and organizations.